f(x) = 2x

g(x) = x + 3

First let us find (fog)(x)

(fog)(x) = f(g(x)

= f(x+3)

= 2(x+3)

= 2x + 6

==> **(fog)(x) = 2x + 6**

Now let us find (gof)(x):

(gof)(x) = g(f(x)

= g(2x)

= 2x + 3

==> **(gof)(x) = 2x + 3**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now